A Comparative Study of Ship Acquisition Projects Through New Shipbuilding, Second-Hand, and Charter Schemes: A Case Study of PT ZZZ - Septiyahardi, Iko; Silvianita (Journal Research of Social Science, Economics, and Management, 2026)
Metallurgical coal (met coal), particularly coking coal, is an essential raw material in steel production. Indonesia, as one of the leading coking coal producers in Southeast Asia, plays a strategic role in supporting the global steel supply chain. Most Indonesian coal exports are transported using tug and barge vessels from rivers to offshore transshipment areas before being transferred to larger vessels for export. This operational pattern presents significant challenges for shipping companies, as river conditions in Indonesia are constrained by depth, cargo capacity, and vessel characteristics. These limitations can affect operational efficiency and financial performance in the shipping sector. This study aims to analyze the investment feasibility of vessel procurement for metallurgical coal transportation at PT ZZZ by comparing three alternative schemes: new shipbuilding, second-hand purchase, and chartering. The analysis employs a quantitative approach using the Discounted Cash Flow (DCF) method, applying Net Present Value (NPV), Internal Rate of Return (IRR), and Profitability Index (PI) as evaluation indicators, based on vessel capital expenditure (CAPEX) and operational expenditure (OPEX) data. New shipbuilding is best for long-term (highest NPV, 70% margin, low risk). Second-hand suits rapid expansion (fastest payback, 32% IRR, moderate risk). Charter needs no CAPEX but has lowest margin (30%) and highest risk, for short-term only. Conclusion: new shipbuilding is optimal for PT ZZZ. The results of this study are expected to serve as a basis for shipping companies in making effective investment decisions that align with operational conditions and enhance financial efficiency.